A framework to assess socioeconomic and spatialized nature-related risks: An application to South Africa - Paul Hadji-Lazaro; Julien Calas; Antoine Godin; Andrew Skowno; Pamela Sekese (Environmental and Sustainability Indicators)
In response to the challenge of biodiversity loss and climate change, understanding the socioeconomic and financial vulnerabilities stemming from the associated physical and transition risks is essential. This paper presents a novel method that integrates ecological and macroeconomic indicators to assess multidimensional socioeconomic nature-related risks at several geographical scales using readily available data. Applying this method to South Africa, we find that 80% of the country's net exports are generated by water-dependent sectors, with 23% originating from water-sensitive municipalities, highlighting significant exposure to water scarcity. Similarly, 51% of mining sector exports are derived from municipalities with ecosystems threatened by mining activities, revealing vulnerabilities tied to transition risks that expose several macro-financial balances. These findings underscore the need for targeted policy interventions to reconcile ecological and economic goals, leveraging complementary insights from ecological and economic disciplines.